2019
DOI: 10.3390/cancers11040484
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Gemcitabine plus Nab-Paclitaxel and FOLFIRINOX in the First-Line Setting of Metastatic Pancreatic Cancer: A Systematic Review and Meta-Analysis

Abstract: Gemcitabine and nab-paclitaxel (GEM-NAB) and the combination of 5-fluorouracil, oxaliplatin, and irinotecan (FOLFIRINOX) are valid first-line options for advanced or metastatic pancreatic cancer (mPC). However, no randomized trials comparing the two schemes have been performed. This meta-analysis aims to compare GEM-NAB and FOLFIRINOX in terms of safety and effectiveness, taking into account data from real-life studies on mPC. We systematically searched PubMed, EMBASE and Cochrane library up to November 2018 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
83
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(87 citation statements)
references
References 34 publications
4
83
0
Order By: Relevance
“…Although our analysis is limited to discuss the overall outcomes of 1L nab-P+ GEM, because we included only 2L population, current findings may indicate that subsequent 2L and 3L chemotherapy may prolong the survival of patients with mPDAC who started 1L nab-P+GEM. Although there is no head-to-head comparative trial, FOLFIRINOX showed numerically better survival outcomes compared to nab-P+GEM in 1L setting [2,3], recent retrospective analyses and meta-analysis in realworld setting have revealed that survival outcomes with these regimens may be similar in mPDAC patients [4,20]. The efficacy of subsequent 2L and 3L chemotherapy after progression on 1L nab-P+GEM shown in our study may contribute to these results.…”
Section: Discussionsupporting
confidence: 48%
“…Although our analysis is limited to discuss the overall outcomes of 1L nab-P+ GEM, because we included only 2L population, current findings may indicate that subsequent 2L and 3L chemotherapy may prolong the survival of patients with mPDAC who started 1L nab-P+GEM. Although there is no head-to-head comparative trial, FOLFIRINOX showed numerically better survival outcomes compared to nab-P+GEM in 1L setting [2,3], recent retrospective analyses and meta-analysis in realworld setting have revealed that survival outcomes with these regimens may be similar in mPDAC patients [4,20]. The efficacy of subsequent 2L and 3L chemotherapy after progression on 1L nab-P+GEM shown in our study may contribute to these results.…”
Section: Discussionsupporting
confidence: 48%
“…Based on 16 retrospective studies that included 2123 gemcitabine plus nab-paclitaxel treated patients and 1690 FOLFIRINOX treated patients, no statistical significantly differences were found in terms of overall risk of death, PFS and RR. Toxicity was in line of the pivotal trials [36]. These results may help to conclude that despite of the numerically superiority in OS of the phase 3 FOLFIRINOX trial when it is compared with MPACT trial, and in the absence of a comparative head to head phase 3 trial for these 2 regimens, clinicians may use any of those according with their experience but also taking account of the medical conditions and biography of each patient to be treated.…”
Section: : Current First-line Options For the Treatment Of Metastmentioning
confidence: 60%
“…Thus, the therapeutic bene ts of FOLFIRINOX were better than GEM-NAB in this cohort. However, previous meta-analysis based on 16 retrospective studies from Italy reported that the survival outcomes were similar between FOLFIRINOX and GEM-NAB [44], with HR for PFS of 0.88 (95% CI 0.71-1.1, p = 0.26) and HR for OS of 0.99 (95% CI 0.84-1.16, p = 0.9). In our meta-analysis, the treatment e cacy was also similar between FOLFIRINOX and GEM-NAB, which was same with previous studies.…”
Section: Discussionmentioning
confidence: 89%
“…Modi ed FOLFIRINOX and GEM-NAB are the most frequently used rst-line treatments for advanced PC. Previous studies have conducted e cacy comparisons between modi ed FOLFIRINOX and FOLFIRINOX [9] or between GEM-NAB and FOLFIRINOX [44], and the outcomes were similar in these comparisons. However, until now, relative effects of modi ed FOLFIRINOX and GEM-NAB treatments are unknown as no direct comparisons have been conducted.…”
Section: Discussionmentioning
confidence: 93%